Individual and joint association of serum 25-hydroxyvitamin D and folate levels with the risk of sarcopenia: a cross-sectional study from the NHANES 2011–2018 - Wei, Yaping; He, Qiangqiang; Di, Qiannan; Li, Jing; Zhang, Jingyi; Na, Lixin (Frontiers in Nutrition, 2025)
BackgroundRecent studies have indicated that vitamin D and folate are essential for muscle health and each is independently linked to the prevalence of sarcopenia. However, the potential synergistic effects of vitamin D and folate on sarcopenia have not been extensively studied. This study aims to investigate both the individual and joint associations of serum 25-hydroxyvitamin D [25(OH)D] and folate concentrations with the risk of sarcopenia.MethodsThis study conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES), covering the years 2011–2018. Multivariable logistic regression models were used to determine individual and joint associations of serum 25(OH)D and folate with sarcopenia. Additionally, the relative excess risk due to interaction (RERI) was estimated to assess additivity.ResultsA significant inverse relationship was observed between serum 25(OH)D and folate levels in relation to sarcopenia. Specifically, among participants with 25(OH)D levels < 50 nmol/L, the odds ratios (ORs) for sarcopenia were 0.67 [95% confidence interval (CI): 0.56–0.81] for those with 25(OH)D levels between 50 and 75 nmol/L, and 0.61 (95% CI: 0.48, 0.77) for those with levels > 75 nmol/L. Similarly, when comparing participants in the lowest tertile of folate, the ORs for sarcopenia were 0.74 (95% CI: 0.61, 0.89) for the second tertile and 0.72 (95% CI: 0.59, 0.88) for the third tertile. Among individuals with fasting blood glucose levels < 7.0 mmol/L, those with both low levels of 25(OH)D and folate exhibited a significantly higher risk of sarcopenia compared to those with high levels of 25(OH)D and folate. Furthermore, the RERI was statistically significant.ConclusionIn the present study, a synergistic interaction between 25(OH)D and folate was observed in relation to the risk of sarcopenia. These findings contribute new insights into the nutritional factors associated with sarcopenia and pave the way for future longitudinal studies to further explore this association.